Outcome of inter-hospital transfer versus direct admission for primary percutaneous coronary intervention: An observational study of 25, 315 patients with ST-elevation myocardial infarction from the London Heart Attack Group. Issue 8 (1st December 2020) - Rathod, Krishnaraj S; Jain, Ajay K; Firoozi, Sam; Lim, Pitt; Boyle, Richard; Nevett, Jo; Dalby, Miles C; Kalra, Sundeep; Malik, Iqbal S; Sirker, Alexander; Mathur, Anthony; Redwood, Simon; et al.
Abstract : Background and aims: In patients with ST-segment elevation myocardial infarction (STEMI), mortality is directly related to time to reperfusion with guidelines recommending patients be delivered directly to centres for primary percutaneous coronary intervention (PCI). The aim of this study was to describe the impact of inter-hospital transfer on reperfusion time and to assess whether or not treatment delays influenced clinical outcomes in comparison with direct admission to a primary PCI centre in a large regional network. Method and results: We undertook an observational cohort study of patients with STEMI treated with primary PCI between 2005 and 2015 in London, UK. Patient details were recorded at the time of the procedure in databases using the British Cardiovascular Intervention Society PCI dataset. The primary end-point was all-cause mortality at a median of 4.1 years (interquartile range: 2.2–5.8 years). Secondary outcomes were in-hospital major adverse cardiac events. Of 25, 315 patients, 17, 560 (69.4%) were admitted directly to a primary PCI centre and 7755 (31.6%) were transferred from a non-primary PCI centre. Patients in the direct admission group were older and more likely to have left ventricular impairment compared with the inter-hospital transfer group. Median time from call for help to reperfusion in transferred patients was 52 minutes longer compared with patients admitted directly ( p <0.001). However, call to first hospital admission was similar. Kaplan–Meier analysis demonstrated significantly lower mortality rates in patients who were transferred directed to a primary PCI centre compared with patients who were transferred from a non-PCI centre (17.4% direct vs . 18.7% transfer, p =0.017). Furthermore, after propensity matching, direct admission for primary PCI was still a predictor of all-cause mortality (hazard ratio: 0.89, 95% confidence interval: 0.64–0.95). Conclusions: In this large registry of over 25, 000 STEMI patients treated by primary PCI survival was better in patients admitted directly to a cardiac centre versus patients transferred for primary PCI, most likely due to longer call to balloon times in patient transferred from other hospitals.